1975
DOI: 10.1073/pnas.72.11.4536
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical characterization of murine H-2 controlled Ss (serum substance) protein through identification of its human homologue as the fourth component of complement.

Abstract: The S region of the mouse H-2 complex is genetically defined by a series of alleles, or pseudoalleles, which control the level of a serum globulin, Ss, and of its allotypic variant, Slp. In contrast with the products of other genes in the complex, no homologue of the Ss protein has been found in other species, except the rat. In the present study, a component in human plasma was identifiedwhich cross-reacts with anti-mouse Ss, and which also displays electrophoretic and size similarities to the mouse Ss protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

1976
1976
1983
1983

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(29 citation statements)
references
References 16 publications
0
28
1
Order By: Relevance
“…Recent work has made it clear that the Ss protein is an antigenic and structural homologue to human C4 (Curman et al 1975;Meo et al 1975;Carroll and Capra 1978;Ferreira et al 1978). However, in this study we observed no correlation of C4 activity with the Ss protein level in serum between Ss' and Ssl strains.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Recent work has made it clear that the Ss protein is an antigenic and structural homologue to human C4 (Curman et al 1975;Meo et al 1975;Carroll and Capra 1978;Ferreira et al 1978). However, in this study we observed no correlation of C4 activity with the Ss protein level in serum between Ss' and Ssl strains.…”
Section: Discussioncontrasting
confidence: 55%
“…Recently, Lachmann et al (1975) and others (Curman et al 1975;Meo et al 1975;Carroll and Capra 1978;Ferreira et al 1978) reported that the Ss protein is mouse C4 molecule. The relationship between the amount of the Ss protein and C4 level in serum was examined in this experiment, and we could find a significant different result between males and females.…”
Section: Measurement Of Each Component Activity Of Some Inbred Strainsmentioning
confidence: 99%
“…Of the 13 propositi in whom no crossover was observed, meiosis was informative in only one parent and therefore a crossover is not ruled out in these children. An increase in intra-HLA recombinants has been observed in juvenile diabetes mellitus (42 (46)(47)(48). In addition, evidence has been presented that C3 level during ontogeny is MHC-linked in mouse (49).…”
Section: Discussionmentioning
confidence: 92%
“…Murine C2 was measured with an identical assay except for the substitution of C2-deficient human serum for the C4DGPS and an incubation time of 1 h. Antisera to Ss and Sip were prepared by standard methods that have been recently described (3,5,13). Goat antiserum to human factor B that cross-reacts with murine factor B was purchased from Atlantic Antibodies, Westbrook, Maine (5).…”
Section: Methodsmentioning
confidence: 99%